LEMBAGA PEMASYARAKATAN KLAS IIA GORONTALO - Kevin Candra; Satar Saman; Berni Idji (Universitas Negeri Gorontalo, 2021)
According to the latest data on the number of inmates per technical implementation unit at the Gorontalo Regional Office, the Gorontalo Class IIA Penitentiary has 585 correctional inmates (or WBP) with a capacity of 330 people. It was found that the prison has an overcapacity of 77%. A number of problems in the penitentiary, such as riots, the escape of inmates, and drug trafficking, are often found. It is caused by the problem of overcapacity, which causes inoptimality of services, supervision, and the entire system implementation. Therefore, it is necessary to rebuild a new prison that can accommodate the entire WBP and is equipped with facilities for the self-development of the WBP. The present research collected secondary data and primary data that can support the process of compiling references for the design of fish landing ports in Gorontalo City. Furthermore, it proceeded with site analysis and building analysis.The results show that the design of Gorontalo Class IIA Penitentiary with the Paradox approach aims to create a closed prison atmosphere for the inmates to reflect on their misconducts and wrongdoings. Meanwhile, the availability of space programs that focus on coaching contributes to create the atmosphere of self-development and self-improvement for the inmates.